Foot-propelled aquatic birds: pelvic morphology and locomotor performance - Ibáñez, B. (2012)
The study of ecomorphology (relationship between morphology, ecology and behavior) and biomechanics (relationship between morphology and function) allows identification of ecomorphs and niche inference. It represents an alternative to classical diversity studies, independent from systematic categories, which allows assessment of ecomorphological assemblages in a given ecosystem - a wetland, in this case - based on shape. In this conceptual framework, twenty species of continental aquatic birds from the Pampean region belonging to Anseriformes, Podicipediformes, Charadriiformes and Pelecaniformes were analyzed. Morphology of the pelvic girdle was analyzed by means of geometric morphometrics, assuming that these are foot-propelled birds. Four ecomorphs were identified, comprising, at one extreme, strictly diving form with very dorsally narrow pelves, and at the other, birds with wide pelves and marked angulation between pre- and postacetabular regions, which are good flyers and dabblers but never dive. © 2012 Copyright 2012 Unione Zoologica Italiana.